A total volatile inventory for Masaya Volcano, Nicaragua - Martin, R; Sawyer, G; Spampinato, L; Salerno, G; Ramirez, C; Ilyinskaya, E; Witt, M; Mather, T; Watson, I; Phillips, J; Oppenheimer, C (2010)
We present results from a campaign in March 2009 to assess the current state of emissions from Masaya Volcano, Nicaragua. These results constitute one of the most comprehensive inventories to date of emissions from an active volcano and update the exceptional record of emissions from Masaya. Results from open-path Fourier transform infrared spectroscopy and filter packs demonstrate that, in terms of H2O, SO2, CO2, HCl, and HF (molar H2O/SO2 = 63, CO2/SO2 = 2.7, SO2/HCl = 1.7, SO2/HF = 8.8), the 2009 gas composition was highly comparable to that from the 1998 to 2000 period, indicating stability of the shallow magma system. This continuity extends to certain aerosol species (molar SO2/SO42- = 190, Na+/SO 42- = 0.68, K+/SO42- = 0.71, Ca2+/SO42- = 1.6 × 10-2, Mg2+/SO42- = 3.6 × 10-3) and, to a lesser extent, the heavy halogens (i.e., molar HCl/HBr = 2.4 × 103, HCl/HI = 5.0 × 104). In contrast to an earlier study at Masaya, we did not detect HNO3. SO2 fluxes were low (690 Mg d-1), suggesting that Masaya was close to the minimum of its degassing cycle. By combining compositional results with the SO2 flux, we estimate a total volatile flux of 14,000 Mg d-1. This rate is consistent with 1-4 wt% volatile loss from a convective magma flux of 17,000-4000 kg s-1. These results will allow for a better understanding of degassing processes at Masaya and other basaltic volcanoes. Copyright 2010 by the American Geophysical Union.